Abatacept in Early Diffuse Cutaneous Systemic Sclerosis: Results of a Phase II Investigator‐Initiated, Multicenter, Double‐Blind, Randomized, Placebo‐Controlled Trial. Issue 1 (10th December 2019) - Khanna, Dinesh; Spino, Cathie; Johnson, Sindhu; Chung, Lorinda; Whitfield, Michael L.; Denton, Christopher P.; Berrocal, Veronica; Franks, Jennifer; Mehta, Bhavan; Molitor, Jerry; Steen, Virginia D.; Lafyatis, Robert; et al.
Abstract : Objective: T cells play a key role in the pathogenesis of early systemic sclerosis. This study was undertaken to assess the safety and efficacy of abatacept in patients with diffuse cutaneous systemic sclerosis (dcSSc). Methods: In this 12‐month, randomized, double‐blind, placebo‐controlled trial, participants were randomized 1:1 to receive either subcutaneous abatacept 125 mg or matching placebo, stratified by duration of dcSSc. Escape therapy was allowed at 6 months for worsening disease. The coprimary end points were change in the modified Rodnan skin thickness score (MRSS) compared to baseline and safety over 12 months. Differences in longitudinal outcomes were assessed according to treatment using linear mixed models, with outcomes censored after initiation of escape therapy. Skin tissue obtained from participants at baseline was classified into intrinsic gene expression subsets. Results: Among 88 participants, the adjusted mean change in the MRSS at 12 months was −6.24 units for those receiving abatacept and −4.49 units for those receiving placebo, with an adjusted mean treatment difference of −1.75 units ( P = 0.28). Outcomes for 2 secondary measures (Health Assessment Questionnaire disability index and a composite measure) were clinically and statistically significantly better with abatacept. The proportion of subjects in whom escape therapy was needed was higher in the placebo group relative to the abatacept group (36% versus 16%). In the inflammatory and normal‐like skin gene expression subsets, decline in the MRSS over 12 months was clinically and significantly greater in the abatacept group versus the placebo group ( P < 0.001 and P = 0.03, respectively). In the abatacept group, adverse events occurred in 35 participants versus 40 participants in the placebo group, including 2 deaths and 1 death, respectively. Conclusion: In this phase II trial, abatacept was well‐tolerated, but change in the MRSS was not statistically significant. Secondary outcome measures, including gene expression subsets, showed evidence in support of abatacept. These data should be confirmed in a phase III trial.